2019
DOI: 10.1007/s00330-019-06525-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of cervical vertebroplasty: report of a large cohort and systematic review

Abstract: Purpose To evaluate retrospectively safety and effectiveness of cervical vertebroplasty (cVP) based on a single centre large cohort. Materials and Methods All cVP performed at single centre from January 2001 to October 2014 were included and reviewed. Procedure-related complications (minor and major) were systematically recorded. Effectiveness in terms of analgesia was evaluated using a semi-quantitative grading scale at one-month follow-up. Risk factors for the occurrence of a procedure-related complication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Mean procedure duration was 57 ± 22 min (range [31-142]). A total of 14 vertebrae (mean 1.3 vertebrae per patient, range [1,2]) were treated (Table 1). Twelve vertebrae (86%) were accessed via a unilateral and two (14%) via a bilateral approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean procedure duration was 57 ± 22 min (range [31-142]). A total of 14 vertebrae (mean 1.3 vertebrae per patient, range [1,2]) were treated (Table 1). Twelve vertebrae (86%) were accessed via a unilateral and two (14%) via a bilateral approach.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to radiation therapy, surgery, and medical treatment, percutaneous vertebroplasty (PV) is now commonly applied to treat pathologic fractures at the cervical and or thoracic levels [1,2]. At the cervicothoracic junction (vertebrae C7, T1, T2, and T3), due to interference from the shoulders, conventional PV with fluoroscopic guidance can be challenging and even impossible [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Five patients of the present study have also been already reported through a study presenting the authors' experience in cervical vertebroplasty (from C1 to C7), reporting the safety and effectiveness of 140 cervical vertebroplasty procedures. 7…”
Section: Patients' Demographic and Lesions' Characteristicsmentioning
confidence: 99%
“…Lesions of the cervical spine account for 8–15% of all spinal metastases 1 , 2 causing intractable pain or numbness and markedly undermining quality of life. Percutaneous vertebral augmentation (PVA), including percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP), is a minimally invasive and promising technique for treating painful cervical spine metastases (PCSMs) 3–6 cited in international guidelines. 7–9 Percutaneous pediculoplasty (PPP), as a non-classical PVA technique, has been applied to patients with vertebral pedicle involvement.…”
Section: Introductionmentioning
confidence: 99%